STRATEGI DINAS KEBERSIHAN DAN PERTAMANAN DALAM MENANGGULANGI KEBERSIHAN DI KOTA PEKANBARU - Santa, Heru; Rusli, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The purpose of this study is to determine how the implementation of trategy Department of Cleanness an Gardens in solving cleanes problems at Pekanbaru City. Pekanbaru City won a competiton as the cleaness city in Indonesia. Pekanbaru also got trophies seven times continuosly. But in this few years, it couldn’t be gotten anymore. Base on the result of this research, it found some factors that influence the implementing the Department of Cleanness an Dardens. Those are the highest number of society, work motivation, lowest of awareness society, the lowest society motivation, loweat control, in last the tools and medium. This research was done in Pekanbaru city. It in Department of Cleanness an Gardens exactly. The population and sample in this research are personnel or employee of Department of Cleanness an Dardens the technique of collecting sample used snowball sampling. The technique of collecting datas used the method of observation, interview and documentation after the data was collected. After coleecting the datas, it is analyzed by using descriptive qualitative analyzed. After doing this research, it found that the implementation strategy of Department of Cleanness an Gardens in solving cleaness problem in Pekanbaru City still did not maximal yet. The strategy of controlling the cleaness is still did not do well. It because the strategies are difficult to implement couse of some problems.Keywords: strategy, controlling of cleaness, factors, implementations